2014
DOI: 10.1021/ma501799z
|View full text |Cite
|
Sign up to set email alerts
|

Does Graphene Change Tg of Nanocomposites?

Abstract: The effect of the addition of graphene on the glass transition temperature (T g) of polymers was investigated, first with poly­(methyl methacrylate) and then with an extensive literature review. Isotactic (i-PMMA) and atactic PMMA (a-PMMA) were blended with pristine graphene (PG) and thermally reduced graphene (TRG). A T g increase was found for a-PMMA nanocomposites made via in situ polymerization with TRG but not when a-PMMA was solvent blended with TRG. However, a T g increase was found for TRG solvent blen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
108
2
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(126 citation statements)
references
References 49 publications
14
108
2
2
Order By: Relevance
“…Accordingly, in the former case the cold crystallization peak, usually observed in the first heating DSC trace is considerably reduced or even suppressed which is in agreement with what is observed in our samples [64]. Moreover, it can be noticed that the glass transition temperature of the polymer was increased by 2e3 C. A recent literature review showed that generally the T g of graphene or GO/polymer nanocomposites is significantly increased (4 C or more) when using functionalized nanofillers, due to the enhancement of their interactions with the matrix [65]. In this view, the interaction of the prepared GO-g-PLA hybrid with the commercial PLA matrix seems to be substantial, even if the PLA chains are short and/or sparsely grafted on the nanofiller surface.…”
Section: Nanocomposite Filmssupporting
confidence: 92%
“…Accordingly, in the former case the cold crystallization peak, usually observed in the first heating DSC trace is considerably reduced or even suppressed which is in agreement with what is observed in our samples [64]. Moreover, it can be noticed that the glass transition temperature of the polymer was increased by 2e3 C. A recent literature review showed that generally the T g of graphene or GO/polymer nanocomposites is significantly increased (4 C or more) when using functionalized nanofillers, due to the enhancement of their interactions with the matrix [65]. In this view, the interaction of the prepared GO-g-PLA hybrid with the commercial PLA matrix seems to be substantial, even if the PLA chains are short and/or sparsely grafted on the nanofiller surface.…”
Section: Nanocomposite Filmssupporting
confidence: 92%
“…However, in the opposite way, incorporating amine-GO nanoplatelets might cleave the original interaction between hard-and soft-segments and hence change the microphase structure in WPU matrix, which will lead to the shift of T g to low temperature. Therefore, the change of nanocomposites in T g compared with pure WPU is not obvious base on the above reciprocal inhibition mechanism [31].…”
Section: Thermal Propertiesmentioning
confidence: 97%
“…However, some published literatures show increases in the T g of the bulk polymer chains upon the addition of GO or graphene [53,54], while others report no obvious change in T g [39,47,55] or even decrease in T g [49]. A very recent study shows that only the covalent attachment of polymer chains onto graphene surface can produce significant restriction on the mobility of the bulk polymer and lead to an increase in the T g [56]. In our work, the variation of T g is in a very narrow region of 1-3°C, which may be considered to be essentially the same.…”
Section: Effects Of Go Size On the Mechanical Properties Of Nr/go Nanmentioning
confidence: 99%